Dissemination of chart information using web-based GIS - Mahmud, Mohd. Razali; Cham, Tau Chia (2005)
With the improvement of electronic technology, many navigational aid systems have been computerized. It is now heading to Web-based GIS technology for efficiency data distribution as to secure the safety of vessel navigation. Web-based GIS holds the potential to make distributed nautical charts information available to a very large worldwide audience. In practice, the Royal Malaysian Navy (RMN) took six months to more than a year to produce a new or updated chart. Therefore, any updates that are important to the users are published in Notice to Mariners by both RMN and Marine Departments monthly. Undoubtedly, this would cause some confusion to the mariners about the reliability of data, as two different departments manage the Notice to Mariners in different formats and timing. Moreover, nautical charts are widely used in offshore engineering works, fisheries industries, and others. All of these parties seek for the latest information about nautical chart in order to success their works. Since the charts are in different format, projection, symbolization and producers, they should be integrated for the needs of safety information. To overcome these problems, it is important to propose Web-based GIS system to manage and visualize nautical charts online. Thus, this paper studies on the creation of Nautical –WebGIS for sharing the charts information throughout Malaysia with the latest Notice to Mariners from both RMN and Marine Departments. The area of this study would be both MAL 5 (Peninsular Malaysia) and MAL 6 (Sabah and Sarawak).The Nautical –WebGIS will enable users to visualize, explore, and perform the queries on nautical charts for needed information.